Does Corporate Governance Moderate Intellectual Capital on Corporate Sustainability Accounting? - Husni, Mohamad dHREW (JURNAL AKUNTANSI DAN AUDITING, 2025)
The impact of intellectual capital on corporate sustainability and governance as a moderating variable is investigated. This research uses the PLS method. This research is about banks on the IDX in 2019-2023.This study demonstrates that structural and physical capital positively and significantly impact firm sustainability. Firm sustainability is significantly impacted negatively by human capital. The sustainability of a firm is not considerably affected by relational capital.  This research strengthens the resource-based view (RBV) theory in the context of the company's intellectual capital where it has unique resources and then creates a competitive advantage. This has practical implications so that companies are in a position to develop exceptional resources that competitors cannot copy, this is in keeping with the RBV view, which emphasises the importance of unique assets in creating competitive advantage.